(untitled) (Journal of Parents and Teachers, 2021)
Three edges converge in Basic Vocational Education and Training: education, social needs and work. A reality that it is not exclusively educational can not be tackled from a educational approach. A reality that it is not exclusively formal can not be tackled from a formal approach either. Only from a systemic perspective, a systemic issue, like this, can be addressed.